2012
DOI: 10.1038/nn.3033
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Homer scaffolds mediate abnormal mGluR5 function in a mouse model of fragile X syndrome

Abstract: Enhanced mGluR5 function is causally associated with the pathophysiology of Fragile X Syndrome (FXS), a leading inherited cause of intellectual disability and autism. Here we provide evidence that altered mGluR5-Homer scaffolds contribute to mGluR5 dysfunction and phenotypes in the FXS mouse model, Fmr1 KO. In Fmr1 KO mice mGluR5 is less associated with long Homer isoforms, but more associated with the short Homer1a. Genetic deletion of Homer1a restores mGluR5- long Homer scaffolds and corrects multiple phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
247
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(266 citation statements)
references
References 50 publications
16
247
1
Order By: Relevance
“…2B). Such lower interaction is also observed in FMR1 knockout and is proposed to lead to constitutive activation of mGlu5 (Ronesi et al, 2012). We also found that the mGlu5-Homer interaction was reduced in wildtype animals after DHPG treatment (P , 0.05, unpaired t test).…”
Section: Glud1 Regulates Mglu5 Signalingsupporting
confidence: 73%
See 3 more Smart Citations
“…2B). Such lower interaction is also observed in FMR1 knockout and is proposed to lead to constitutive activation of mGlu5 (Ronesi et al, 2012). We also found that the mGlu5-Homer interaction was reduced in wildtype animals after DHPG treatment (P , 0.05, unpaired t test).…”
Section: Glud1 Regulates Mglu5 Signalingsupporting
confidence: 73%
“…Homer proteins are known to link mGluRs to other postsynaptic density proteins (Shiraishi-Yamaguchi and Furuichi, 2007;Niswender and Conn, 2010) and play a vital role in coupling the receptors with downstream effectors (Mao et al, 2005;Jung et al, 2007;Won et al, 2009). Disrupted interaction between mGlu5 and the long isoform of Homer leads to deficits in mTOR signaling, protein translation, as well as synaptic plasticity in the FMR1 knockout mouse model (Ronesi and Huber, 2008;Ronesi et al, 2012). We found that the Akt-mTOR phosphorylation was increased under basal conditions in the GluD1 KO.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Most notably, FMRP knock-out (KO) mice have increased levels of protein synthesis and show enhanced mGluR-dependent long-term depression (mGluR-LTD) in the hippocampus [27] as well as impaired long-term potentiation (LTP) in the amygdala [28,29]. It has been shown that the synaptic-level symptoms in these mice are caused by increased sensitivity to mGluR5 signalling and extracellular signal-regulated kinase (ERK)-1/2 [30], and that this is related to a disrupted balance of Homer isoforms [31]. In addition to this, TSC1, a negative regulator of mammalian target of rapamycin (mTOR), which is upstream of FMRP, has been implicated in autistic symptoms through tuberous sclerosis (TSC) [32][33][34], and also tested in a mouse model [18].…”
Section: The Synaptic Theory Of Autismmentioning
confidence: 99%